PEMENUHAN HAK-HAK PEKERJA PADA HOME INDUSTRY BULU MATA PALSU - Windiarti, Lisa; Wardani, Susilo (LPPM STIH Awang Long, 2025)
Entrepreneurs in the informal sector of the false eyelash home industry in Padamara Sub-District, Purbalingga Regency, have made efforts to comply with basic legal requirements through the possession of a Business Identification Number (NIB). However, several home industries in this area still lack NIBs, resulting in limited access to legal recognition and business protection. This study aims to analyze the fulfillment of workers rights in the false eyelash home industry in Padamara Sub- District, Purbalingga Regency, and to identify the factors that hinder these businesses from obtaining legal permits. The research employs both normative juridical and empirical juridical methods. Thenormative juridical approach is conducted through literature review, including books, journals, and relevant legislation. The empirical juridical method involves interviews with key informants to obtain primary research data. The findings reveal two main points: First, the fulfillment of workers normative rights does not yet align with Law Number 13 of 2003 concerning Manpower. This includes issues such as the right to a fair wage, reasonable working hours, absence of clear and written employment agreements, and lack of occupational safety and health protectionslargely due to the informal status of these workers. Second, several factors hinder the fulfillment of workers rights in the false eyelash home industry in Padamara, including the lack of legal incorporation of these businesses, limited understanding among business owners regarding the importance of legal registration, perceptions that licensing processes are complex and costly, and the prevailing subcontracting and nonpermanent work system. Moreover, cooperatives, which serve as the operational platform for these businesses, also contribute to the slow progress in formalizing these enterprises.